Esoteric Imperialism: The Solomonic-Theurgic Mystique of John Dee's British Empire. Issue 1 (March 2019) - Arnold, Jafe
Highlights: Explores the vision of a British Empire of the English Renaissance polymath, John Dee (1527–1609), in its historical and intellectual contexts. Highlights the connections between Dee's vision of a British Empire and Dee's occult, magical, and political pursuits. Reviews how scholarship has increasingly reconstructed the centrality of Dee's "Cosmopolitics" to his worldview, biography, and era. Suggests that further research into Dee's "esoteric imperialism" can shed light on the context, content, and networks of Dee's British Empire. Abstract: The life and works of the English Renaissance polymath John Dee (1527–1609) have been traditionally treated by scholarship in the context of the history of philosophy and science. Only in recent decades have two of John Dee's most prominent and controversial endeavors - (1) his political philosophy and advocacy of a British Empire (a term he is credited with coining), and (2) his long-standing practice of angelic magic - been reconstructed in their significance to Dee's worldview. This paper highlights how Dee's visions of a British Empire and his angelic rituals were not only major landmarks in his corpus, but were intimately interconnected in Dee's ideology of "Cosmopolitics." Dee's "esoteric imperialism" is situated in the context of his intellectual, textual, and political environment, and his angelic magic is identified as fitting within the medieval Solomonic current. It is argued that both ideological trends coalesced in Dee's vision of an angelic-inspired British Empire.